In nomen omen: the effect of flower distance on female reproductive success of the lax-flowered orchid Anacamptis laxiflora (Orchidaceae). (15th January 2021) - Scopece, Giovanni; Criscuolo, Nicola; Cozzolino, Salvatore
Abstract: Aims: In multiflowered species, the architecture of inflorescences is of primary importance in shaping plant attractiveness. The aim of this study was to disentangle the role of inflorescence traits in plant female reproductive success and pollination patterns along the inflorescence in the lax-flowered orchid Anacamptis laxiflora, a terrestrial species exploiting a deceptive pollination strategy. We also evaluated whether the relationship between inflorescence traits and female reproductive success was modified by the height of surrounding vegetation and/or by population density. Methods: We delimited experimental plots in a natural population of A. laxiflora . We tallied the individuals within each plot and categorized low-density plots and high-density plots; then, in part of the plots we manually removed surrounding grass thus producing an equal number of plots with high grass and low grass. Within these plots, we recorded inflorescence traits and female reproductive success (i.e. the number of fruit and their position along the inflorescence). We analyzed these data using generalized linear mixed-effects models (GLMMs) and calculated selection gradients. Important Findings: We found that all the investigated inflorescence traits influenced female reproductive success. In particular, our GLMMs showed that 'average flower distance' was the best predictor for shaping reproductive success patterns. We detected significant positive selection on the investigated inflorescence traits, but these selective trends were strictly linked to both the height of the surrounding vegetation and the population density, suggesting a significant influence of local environmental context in shaping selective patterns. Female reproductive success was not linked to the position of flowers along the inflorescence, suggesting that pollinators visit flowers randomly along the inflorescence without a detectable preference for a specific part. This study highlights the importance of inflorescence traits in shaping female reproductive success of multiflowered deceptive orchids, and confirms a primary role for the environmental context in modifying pollinator-mediated selection patterns.